2003
DOI: 10.1016/s0378-1097(03)00756-0
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistantPseudomonas aeruginosastrains harbouring R-plasmids and AmpC β-lactamases isolated from hospitalised burn patients in a tertiary care hospital of North India

Abstract: The present study was designed to determine resistance rates and patterns in Pseudomonas aeruginosa isolates obtained from hospitalised burn patients in an Indian tertiary care hospital. To that end, we isolated plasmid(s) from the multidrug-resistant isolates, demonstrated the plasmid-mediated resistance by curing and transformation experiments, and screened all the isolates for the occurrence of AmpC L-lactamases. Thirty isolates of P. aeruginosa were analysed for the presence of antibiotic resistance. Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 13 publications
(19 reference statements)
5
32
1
Order By: Relevance
“…Pseudomonas aeruginosa plays an important aetiological role in human infections as many clinical isolates are resistant to common antibiotics [14,15]. The prevalence of P.aeruginosa infection in our study 316/2076 (15.22%) were similar to (18.2%) studies of Gad et al, [16].…”
Section: Discussionsupporting
confidence: 88%
“…Pseudomonas aeruginosa plays an important aetiological role in human infections as many clinical isolates are resistant to common antibiotics [14,15]. The prevalence of P.aeruginosa infection in our study 316/2076 (15.22%) were similar to (18.2%) studies of Gad et al, [16].…”
Section: Discussionsupporting
confidence: 88%
“…and 37% of E. coli in Chennai [23]. Around the same time, Shahid et al reported 20 P. aeruginosa isolates as producing AmpC beta lactamases in Aligarh [18]. In 2005, data from Chennai revealed AmpC production in 20.8% Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid curing experiments was also preformed as described by Shahid et al [18]. Ethidium bromide was used as the curing agent.…”
Section: Plasmid Analysis and Curing Experimentsmentioning
confidence: 99%
“…A limited number of studies have analyzed drug resistance in P. aeruginosa plasmid-mediated AmpC β-lactamase. In 2003, Shahid et al (23) isolated P. aeruginosa strains exhibiting plasmid-mediated AmpC enzyme from burns patients in an intensive care hospital in Northern India. In the domestic environment, a single strain of E. coli was previously observed to exhibit ACT-1 plasmid AmpC enzyme.…”
Section: Discussionmentioning
confidence: 99%